Effect of Annona muricata pre-treatment on liver synthetic ability, kidney function and hematological parameters in dimethylnitrosamine (DMN)-administered rats - Usunobun, Usunomena; Okolie, Ngozi (International Journal of Medicine, 2016)
Background:Dimethylnitrosamine (DMN) is a potent hepatotoxin, carcinogen and mutagen which exerts carcinogenic effects and induces hepatic necrosis in experimental animals through metabolic activation by CYP2E1. This study thus evaluated efficacies of Annona muricata pre-treatment on acute dimethylnitrosamine (DMN)-induced anemia and biochemical alterations in male albino rats.Methods:Four (4) groups of six (6) rats each were used for the study. Group 1 served as control and was untreated, group 2 and 3 were pre-treated with 400mg/kg Annona muricata ethanol leaf extract for one week while group 3 and 4 each received single dose of 20mg/kg DMN (orally) after one week. The rats were sacrificed 48hrs after DMN administration.Results:In rats administered 20mg/kg DMN, toxicty was clearly shown by decreased activities of serum liver synthetic molecules namely total protein, albumin, increased total bilirubin, increased kidney parameters such as creatinine and urea as well as decreased body weight gain. The toxic effect of DMN was also indicated by significantly decreased levels of red blood cells (RBC), hemoglobin (Hb), packed cell volume (PCV), white blood cells (WBC) and platelet count (Plt count). However, in rats pre-treated with 400mg/kg Annona muricata prior to DMN administration, there were significant reversals in the activities of serum liver synthetic molecules, kidney profiles, and hematological parameters when compared to DMN-alone administered rats.Conclusion:Annona muricata pre-treatment exhibited in vivo protective and anti-anemic effects against DMN-induced injury.